Enhanced Microwave Electric Field Measurement With Cavity-Assisted Rydberg Electromagnetically Induced Transparency - Li, Shaohua; Yuan, Jinpeng; Wang, Lirong; Xiao, Liantuan; Jia, Suotang (Frontiers in Physics, 2022)
We report a scheme for enhancing microwave electric field measurement by cavity-assisted Rydberg electromagnetically induced transparency (EIT) in a 87Rb coherent atomic system. The vacuum Rabi splitting appears when the probe field is strongly coupled with intracavity atoms. The cavity-assisted EIT with dual-peak profile is observed as a strong coupling laser is further introduced into the optical ring cavity. The optimal atomic density, resulting an appropriate vacuum Rabi splitting interval and cavity-assisted EIT amplitude, is determined for the coupling effect criterion of probe field and intracavity atoms. Finally, the cavity-assisted EIT is employed to accurately measure the microwave electric field strength, and a factor of 2 measurement sensitivity is improved owing to enhanced photon-atom interaction. This work is beneficial for the development of compact, broadband and self-calibrating microwave receivers.